Handbook of Lifelong Learning for Sustainable Development (World Sustainability Series, 2018)
This book focuses on lifelong learning for sustainable development, an aspect that has been rarely explored in great detail. It also discusses methodological approaches and experiences deriving from case studies and projects, which demonstrate how lifelong learning for sustainable development can be implemented in practice. The book provides respecting research institutions, universities, NGOs, and enterprises with an opportunity to display and present their work in this field. It fosters the exchange of information, ideas and experiences acquired in the context of concerning initiatives, especially with regard to successful projects and best practices.